Brief contact interventions in sport psychology - Archer, Mark; Virtual Brands; Del Padre Visual Productions ([Wilbraham, Mass.] : Virtual Brands, 2002)
This video shows sport psychology consultants working with athletes in naturalistic sport environments. The video provides vivid demonstrations of the sport psychology wquivalent of first aid in practice, precompetitive, and postcompetitive contexts
Title from title screen
Executive producer, Judy Van Raalte, Al Petitpas, Britt Brewer ; camera, Geoff Alson, Mark Archer, Orlando Ramos
Host: Al Petitpas
Consultants: Burt Giges, Kenneth Ravizza, Judy Van Raalte, Leonard Zaichkowsky
Keywords: Sports -- Psychological aspects; Athletes -- Psychology